Beliefs and Attitudes Toward Inclusion of Student Teachers and Their Contact With People With Disabilities - Kunz, André; Luder, Reto; Kassis, Wassilis (Frontiers in Education, 2021)
Inclusive schooling has been a key issue in special needs education for the last twenty years (UN-BRK, United Nations, 2006). In this context, teacher’s attitudes towards inclusion is a essential factor in professional competence (Baumert and Kunter 2006). It is therefore in the interest of an inclusive school system that inclusion-related beliefs and attitudes are cultivated in basic teacher education (Forlin et al. 2011). Although some studies report positive effects of basic teacher education on successful inclusion processes and outcomes at school (Ruberg and Porsch 2016), the findings on attitude changes in teacher education are inconsistent (Avramidis and Norwich 2002; de Boer 2011; Sze 2009). Multiple factors influence inclusion-related attitudes and beliefs. Among them, personal contact with people with disabilities is important (Forlin et al. 2010). The present study at the University of Teacher Education in Zurich, Switzerland, examines the influence of previous contact with people with disabilities on attitudes toward inclusion after initial teacher training modules. An online survey (N = 443) was conducted before (T0) and after (T1) a training module on inclusive education/inclusive teaching. Validated scales on attitudes towards inclusion were used. The findings show that the students report significantly more positive contact with people with disability than negative ones. At the same time, students who are in contact with people with disabilities report a significantly more positive attitude towards inclusion at the beginning of the term, and a higher self-efficacy in dealing with disruptive behavior and interdisciplinary cooperation, as well as an individualizing teaching structure. They also report fewer concerns and negative attitudes than students without such contact. Contact with people with disabilities was significantly related to an anticipated willingness to take on an inclusive class. However, no moderating effect of contact over the term was found. Additionally, we identify a considerable heterogeneity on positive attitudes towards inclusion within the respective groups (i.e., more positive or negative contact) via multigroup latent profile analysis. In particular, higher levels on self-efficacy in dealing with disruptive behavior and individualizing teaching structure were central indicators for positive attitudes towards inclusion; this held for both contact groups.